2018
DOI: 10.3389/fmed.2018.00218
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Story of Autoantibodies in Pemphigus Vulgaris: Development of the “Super Compensation Hypothesis”

Abstract: Emerging data and innovative technologies are re-shaping our understanding of the scope and specificity of the autoimmune response in Pemphigus vulgaris (PV), a prototypical humorally mediated autoimmune skin blistering disorder. Seminal studies identified the desmosomal proteins Desmoglein 3 and 1 (Dsg3 and Dsg1), cadherin family proteins which function to maintain cell adhesion, as the primary targets of pathogenic autoAbs. Consequently, pathogenesis in PV has primarily considered to be the result of anti-Ds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 182 publications
0
54
0
2
Order By: Relevance
“…[12,17,20,25] The development of new techniques for measuring Abs has resulted in the identification of a large number of autoantigens with detectable autoAbs in the sera of patients with pemphigus and other autoimmune diseases. [32] Although numerous in vitro and in vivo animal studies have demonstrated that disruption of acetylcholine receptor function (nicotinic and muscarinic AChR) results in acantholysis similar to that seen in pemphigus, the exact role of these autoAbs in the clinical manifestations of pemphigus in man is unclear. [33] Recently, Lakshmi and co-workers reported that patients with PV and PF had significantly higher titers of IgG anti-M3AChR than normal controls, as well as Abs against DSG1 and DSG3.…”
Section: Discussionmentioning
confidence: 99%
“…[12,17,20,25] The development of new techniques for measuring Abs has resulted in the identification of a large number of autoantigens with detectable autoAbs in the sera of patients with pemphigus and other autoimmune diseases. [32] Although numerous in vitro and in vivo animal studies have demonstrated that disruption of acetylcholine receptor function (nicotinic and muscarinic AChR) results in acantholysis similar to that seen in pemphigus, the exact role of these autoAbs in the clinical manifestations of pemphigus in man is unclear. [33] Recently, Lakshmi and co-workers reported that patients with PV and PF had significantly higher titers of IgG anti-M3AChR than normal controls, as well as Abs against DSG1 and DSG3.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence suggesting that anti-Dsg autoantibodies cannot account for the loss of cellcell adhesion seen in PV, indicating that multiple combinations of pathogenic or subpathogenic autoantibodies may function together to contribute to acantholysis. "Desmoglein compensation hypothesis" and "steric hindrance theory" are the widely recognized pathogenic mechanisms of pemphigus [20][21][22][23].The formation of blisters in PV is due to the synergistic effect of autoantibodies targeting multiple keratinocyte antigens [24,25]. For example, in addition to Dsg, a variety of other autoantibodies have been described in PV, including cholinergic receptors [26], anti-mitochondrial Proteins [27], non-Dsg adhesion proteins (desmocollin and plakophillin) [28,29], and additional targets related to γδ-T lymphocytes, ATP2C1 and IL-36 [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…"Desmoglein compensation hypothesis" and "steric hindrance theory" are the widely recognized pathogenic mechanisms of pemphigus [21][22][23][24]. The formation of blisters in PV is due to the synergistic effect of autoantibodies targeting multiple keratinocytes antigens [25,26]. For example, in addition to Dsg, a variety of other autoantibodies have been described in PV, including cholinergic receptors [27], anti-mitochondrial Proteins [28], non-Dsg adhesion proteins (desmocollin and plakophillin) [29,30], and additional targets concerning γδ-T lymphocytes, ATP2C1 and IL-36 [31][32][33].…”
Section: Discussionmentioning
confidence: 99%